The Role of Simplified Enterprise Architecture (Mini TOGAF) in Improving Project Management Governance and Decision-Making - Budianto, Farhan Alif; Lubis, Muharman; Mukti, Iqbal Yulizar; Budianto, Setyo (International Journal of Advances in Data and Information Systems, 2025)
The development of information technology in the digital age requires companies to have a system architecture that is aligned with their business strategy. One commonly used framework is The Open Group Architecture Framework (TOGAF). However, the complexity of TOGAF is often an obstacle to its implementation, especially for organizations with limited resources. This study introduces a Mini TOGAF framework—an adaptive simplification of TOGAF 10 artifacts—designed specifically for digital creative enterprises. Unlike previous simplification models that mainly addressed SMEs in traditional industries, this framework integrates agile principles and stakeholder-centered validation cycles, reflecting the current evolution of enterprise architecture practice in 2023–2025. The method used is Design Science Research (DSR) with three main cycles: the Relevance Cycle to identify organizational needs, the Rigor Cycle to review relevant theories and methods, and the Design Cycle to iteratively design and evaluate artifacts. Data was collected through interviews, observations, and literature studies, then validated by the company. The results of the study show that the application of Mini TOGAF can improve architectural understanding, operational efficiency, business agility, and corporate strategy alignment. The simplification of TOGAF artifacts has been proven to reduce the complexity of implementation without reducing the main benefits of the framework. This study contributes to enterprise architecture literature by proposing an adaptive TOGAF 10 simplification model that strengthens the theoretical link between architectural governance and digital business agility. These findings provide practical contributions for organizations in adopting Enterprise Architecture efficiently and adaptively to modern business needs.